Sistem Peminjaman Loker Otomatis Menggunakan QR Code dan Arduino - William Winarto; Alexander Setiawan; Resmana Lim (Jurnal Infra, 2020)
Bank locker is a much needed facility, especially in public places. The lack of these bank lockers are very unsettling for those who carry a lot of luggage. From those many locker lending places in Indonesia, mostly still operated manually or using human labor. In the current era of globalization, automation is a major demand in all fields of work. Therefore, an automatic locker loan system is created from combining arduino WeMos D1 mini and android application. Android application is created using Android Studio, whereas the arduino is coded with Arduino IDE. The result of research showed that the integration of arduino and android application was successful in terms of automation and effectiveness.